Women, gender and everyday social transformation in India - Nielsen, Kenneth Bo; Waldrop, Anne (Anthem South Asian studies., 2014)
The pace of socioeconomic transformation in India over the past two and a half decades has been formidable. This volume sheds light on how these transformations have played out at the level of everyday life to influence the lives of Indian women, and gender relations more broadly. Through ethnographically grounded case studies, the authors portray the contradictory and contested co-existence of discrepant gendered norms, values and visions in a society caught up in wider processes of sociopolitical change. 'Women, Gender and Everyday Social Transformation in India' moves the debate on gender and social transformation into the domain of everyday life to arrive at locally embedded and detailed, ethnographically informed analyses of gender relations in real-life contexts that foreground both subtle and not-so-subtle negotiations and contestations.